The Historical View of Banking System in Greece During the Financial Crisis - Challoumis, Constantinos; Eriotis, Nicolaos (Journal of Ecohumanism, 2024)
This paper explores the complex dynamics of Greece’s banking system amid the financial crisis that deeply impacted both the nation and the global economy. Anchored in two primary objectives, the research investigates the roots of the crisis that destabilized the Greek financial sector and assesses the broader implications of the eurozone crisis, which reverberated internationally. This analysis reveals a confluence of domestic and global catalysts that spurred a severe credit contraction and disruption within Greece’s banking industry. In response to the unfolding crisis, Greek banks undertook an extensive, globally-oriented examination, utilizing data from major financial centers worldwide to mitigate the crisis’s impact and foster resilience. The study also expands its scope to examine the cross-border interconnectedness of the financial system, which allowed actions in other countries to amplify the economic turmoil in Greece. This work further emphasizes the humanitarian consequences of economic crises, addressing the societal and personal hardships endured and advocating for empathy as a crucial component of economic recovery. Ultimately, this research underscores the need for a global perspective, resilience strategies, and compassionate policies to effectively manage and recover from financial crises.